A Gentle Breeze on the Wheels of Fair Justice for Women in Bangladesh: An Empirical Evaluation of Family Courts’ Mediation Underpinning Rawls’ Theory of Justice - Chowdhury, Jamila A; Eusuf, Ifat Mubina (Dhaka University Law Journal, 2021)
Abstract not available Dhaka University Law Journal, Vol. 31, 2020 P.63-84